2020
DOI: 10.1093/europace/euaa105
|View full text |Cite
|
Sign up to set email alerts
|

Exercise restriction is protective for genotype-positive family members of arrhythmogenic right ventricular cardiomyopathy patients

Abstract: Aims In arrhythmogenic right ventricular cardiomyopathy (ARVC) patients, exercise worsens disease course, so exercise restriction is recommended. However, recommendations for genotype-positive ARVC family members is incompletely resolved. We aimed to provide evidence for exercise recommendations for genotype-positive ARVC family members. Methods and results Arrhythmogenic right ventricular cardiomyopathy family members inheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…This is in line with a recent study reporting a strong association between exercise dose and definite AC criteria and VA in mutation-positive family members, and this association was more prominent in females. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with a recent study reporting a strong association between exercise dose and definite AC criteria and VA in mutation-positive family members, and this association was more prominent in females. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Exercise dose was also assessed dichotomized as below or above 12.5 MET h/week, based on the American Heart Association/American College of Sports Medicine recommendations 16 and a recent publication on exercise restriction in genotype-positive AC family members. 17 High-intensity exercise was defined as >6 METs. 16 Athletes were defined as exercise doses equivalent to ≥4 h of high-intensity exercise per week according to a previously used definition of athletic activity.…”
Section: Methodsmentioning
confidence: 99%
“… 47 Among relatives of patients with ARVC with P/LP desmosomal variants, exercise increases penetrance and risk of incident arrhythmias, but not all athletic relatives develop ARVC. 48 . Additionally, a recent study 49 showed 0.23% of a general clinical population harbored a loss of function desmosomal variant.…”
Section: Discussionmentioning
confidence: 99%
“…Management strategies focus on symptom relief, slowing disease progression and prevention of arrhythmias and SCD [ 11 ]. In addition, lifestyle interventions and in particular exercise restriction are recommended [ 12 ]. Exercise is an important risk factor.…”
Section: Clinical Featuresmentioning
confidence: 99%